2018
DOI: 10.1038/s41467-018-06563-w
|View full text |Cite
|
Sign up to set email alerts
|

Lévy-like movement patterns of metastatic cancer cells revealed in microfabricated systems and implicated in vivo

Abstract: Metastatic cancer cells differ from their non-metastatic counterparts not only in terms of molecular composition and genetics, but also by the very strategy they employ for locomotion. Here, we analyzed large-scale statistics for cells migrating on linear microtracks to show that metastatic cancer cells follow a qualitatively different movement strategy than their non-invasive counterparts. The trajectories of metastatic cells display clusters of small steps that are interspersed with long “flights”. Such move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 71 publications
(144 reference statements)
7
82
0
Order By: Relevance
“…However, extensive work has shown that cancer invasion, at least in its initial steps, is largely non-destructive, without significant tissue remodeling, and that malignant cells can traffic through pre-existing interstitial spaces, which likely serve as routes of least resistance. [22][23][24][25][26] In keeping with this work, our findings, as shown in Fig. 10, may explain some features of classically recognized cancer behavior such as tumor cell spread within an organ tissue plane (single-cell filing of lobular carcinoma of the breast, linitis plastica of the stomach and, as shown in this study, periductal spread of cholangiocarcinoma).…”
Section: Discussionsupporting
confidence: 89%
“…However, extensive work has shown that cancer invasion, at least in its initial steps, is largely non-destructive, without significant tissue remodeling, and that malignant cells can traffic through pre-existing interstitial spaces, which likely serve as routes of least resistance. [22][23][24][25][26] In keeping with this work, our findings, as shown in Fig. 10, may explain some features of classically recognized cancer behavior such as tumor cell spread within an organ tissue plane (single-cell filing of lobular carcinoma of the breast, linitis plastica of the stomach and, as shown in this study, periductal spread of cholangiocarcinoma).…”
Section: Discussionsupporting
confidence: 89%
“…As 1 < < 2 for all concentrations (inset of figure 2C), the migrating cells are super-diffusing which is a sign of active motility and in agreement with prior findings e.g. Takagi et al 2008, Huda et al 2018. Thus, the investigated cells appear to overcome the steric hindrances, i.e.…”
Section: Super-diffusive Migrationsupporting
confidence: 90%
“…For each of the migrating cells' trajectories, this model estimates the persistence time, , along the primary axis of migration, p. The distributions of shown in figure 5A signify stochastic spreading dynamics with long ranged displacements Hallatschek and Fisher 2014. It has previously been reported that metastatic cancer cells do not only move in a super-diffusive fashion, but also display movement patterns consistent with Lévy walks Codling et al 2008, Huda et al 2018. We, thus, considered both power law (Lévy), exponential (Brownian) as well as log-normal models, which have been found to fit the motion of T-cells within lymph nodes Fricke et al 2016.…”
Section: Identifying Super-spreadersmentioning
confidence: 99%
“…Theoretical studies have shown that the optimal searching strategy can change as a function of the ecological context, such as the density of targets, risk of predation, and kinds of objects being sought [54,55,56,57,58]. Some empirical studies have reported that animals do not always exhibit Lévy walks [4,5,3]. It is therefore possible that the plasticity of spontaneous behavior caused by changing the coupling strength of the systems can lead to adaptive responses to environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Lévy walks are a special class of random walks with step lengths that follow a power-law distribution P ( ) ∼ −µ where µ ∈ (1, 3] is a power-law exponent. Lévy walks are observed in a variety of biological movements and agents, ranging from cells and insects to mammals, humans, and even memory retrievals in human cognition [1,2,3,4,5,6,7,8]. Lévy walks are composed of many short steps and rare, long straight movements.…”
Section: Introductionmentioning
confidence: 99%